Dampak Penggunaan Faceswap Bagi Pengguna Media Sosial - M.Thoif Setiawan; R. Joko Musridho; Desri Insani; Selvi Widya Rahmi (PT Pustaka Cendekia Group, 2024)
FaceSwap technology, which allows digital face swapping in photos and videos, has become a rapidly growing global phenomenon on various social media platforms. The use of FaceSwap not only provides opportunities for creativity and visual entertainment, but also raises serious concerns about privacy, digital ethics, and psychological impacts on its users. This article aims to explore social media users' perceptions of FaceSwap technology, especially from a social and psychological perspective. The methodology used is quantitative descriptive research through the distribution of questionnaires to 100 respondents who are active social media users in Indonesia. The results showed that 66% of respondents used FaceSwap for entertainment purposes, but 1% expressed discomfort when their faces were used without permission. In addition, 44% had received misleading FaceSwap content. This article recommends the need to strengthen digital literacy and the formation of clear policies and regulations to protect users' privacy rights and digital identities in the era of AI-based technology.